2015
DOI: 10.1177/0019793915619904
|View full text |Cite
|
Sign up to set email alerts
|

Did Employers in the United States Back Away from Skills Training during the Early 2000s?

Abstract: A number of recent studies suggest that employer-paid training is on the decline in the United States. The present study provides empirical evidence on the issue by analyzing data on employer-paid training from the Survey of Income and Program Participation, a nationally representative data set. The findings reveal a 28% decline in the incidence of training between 2001 and 2009. Very few industries were immune from the decline, and the pattern was evident across occupation, education, age, job-tenure, and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…Although employees likely benefit, again the question is whether self-interested employers would invest in training or career ladders. Representative data are scarce, but our best evidence shows a decline in employer investments in training (Waddoups 2016). Based on SIPP data, the fraction of respondents who received company-provided training fell from 21% to 12% between 1996 and 2008 (White House Report 2015: 16).…”
Section: Does the High Road Pay Off?mentioning
confidence: 90%
“…Although employees likely benefit, again the question is whether self-interested employers would invest in training or career ladders. Representative data are scarce, but our best evidence shows a decline in employer investments in training (Waddoups 2016). Based on SIPP data, the fraction of respondents who received company-provided training fell from 21% to 12% between 1996 and 2008 (White House Report 2015: 16).…”
Section: Does the High Road Pay Off?mentioning
confidence: 90%
“…This suggests that the traditional interest in firm-sponsored training is not only still relevant but may even be growing in importance . 3 There is a striking finding in Waddoups (2016) who found that in the US between 2001 and 2009 there was '… a 28 per cent decline in the incidence of training … Very few industries were immune from the decline, and the pattern was evident across occupation, education, age, job-tenure, and demographic groups.' More critically, the study found that '… the workforce appears to have had the educational credentials by 2009 that, had they occurred in 2001, would have led to substantially more training.'…”
Section: Introductionmentioning
confidence: 99%
“…This may have been caused by too much work, too many obligations, and a lack of organizational support. According to Waddoups (2016), only 17% of workers receive organizational and supervisory support for training, reaffirming that most organizations do not use and support MOOCs for professional development. To get support from supervisors and organizations, employees may pursue certificates through MOOCs since some employers are willing to pay for certificates and will support such types of professional development (Hamori, 2019).…”
Section: Different Tailored and Effective Interventionsmentioning
confidence: 97%